Effect of School Food Service on Achievement in Health Education among junior secondary school students (JSS) in Orlu Local Government Area in Imo State - Onuoha, Roseline Chizoba; Omeje, Chinenye B. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2024)
The study was carried out to ascertain the effect of school food services on achievement of health education among secondary students in Orlu Local Government in State. To guide the study, two research questions and two null hypotheses were formulated respectively. The population for the study comprised 3850 JSS11 students from 254 state owned secondary school in Imo State in 2023/2024 academic session. A sample size of 154 JSS11 students comprising 72 students each were used in the experimental group and control group respectively. Health Education Achievement Test (HEAT) was developed by the researchers and was used for data collection. Five experts validated the instrument which gave a reliability coefficient of 0.78. Mean and standard deviation for answering the research questions while Analysis of Covariance was used to test the null hypotheses at 0.05 level of significance. The results revealed that students who received school food services in the experimental group performed better than students in control group and there was a significant difference between mean scores of students who partook in-school food services. Thus, school food services have relative effect on students’ performance. Based on the findings of the study, it was recommended among others that students should be provided with school food services since it enhances students’ academic achievement of health education in the secondary schools.